2019
DOI: 10.1111/jphs.12281
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control through pharmaceutical care: a meta-analysis of randomized controlled trials

Abstract: Objectives To evaluate the effect of pharmaceutical care (PC) on glycemic control in patients with type 2 diabetes mellitus. Methods A systematic search of literature was conducted to identify randomized controlled trials (RCTs) in patients with type 2 diabetes mellitus. RCTs published in English between January 2011 and November 2015 were identified using nine electronic databases: MEDLINE, International Pharmaceutical Abstracts (IPA), EMBASE, Scopus, Science Direct, Cochrane Library, Web of Science, Springer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Despite varied settings, healthcare models and population groups, several systematic reviews have demonstrated the favourable impact community pharmacy interventions have on both clinical and patient-related outcomes (online supplementary table 2). 27–35…”
Section: Community Pharmacy Interventions In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite varied settings, healthcare models and population groups, several systematic reviews have demonstrated the favourable impact community pharmacy interventions have on both clinical and patient-related outcomes (online supplementary table 2). 27–35…”
Section: Community Pharmacy Interventions In Diabetesmentioning
confidence: 99%
“…The duration of interventions has typically ranged from 3 months to 12 months, while the follow-up period has ranged from 1 month to 4 years 35 37. There is conflicting evidence as to whether duration predicts effect32 34 35 but it has been proposed that frequency of contact is most important 39…”
Section: Community Pharmacy Interventions In Diabetesmentioning
confidence: 99%